Fructose-ammonium dihydrogen phosphate environment-friendly adhesive as well as preparation method and application thereof

By adding components such as ammonium dihydrogen phosphate and ternary composite crosslinking agent to the glycosyl adhesive, the problems of low pH, high viscosity, and glue penetration in plywood applications are solved, and higher pH, moderate viscosity and stronger glue strength are achieved, improving the performance and industrial application potential of plywood.

CN119639421APending Publication Date: 2025-03-18NANJING FORESTRY UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411901399.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The application of existing sugar-based adhesives in plywood has problems such as small pH value, large viscosity, easy glue seepage, and low curing efficiency, resulting in reduced brittleness of the sheet, insufficient glue strength and difficulty in industrial application.

Method used

By introducing components such as ammonium dihydrogen phosphate, ternary composite crosslinking agent, diphenylmethane diisocyanate and epoxy resin, the pH value and viscosity of the adhesive are adjusted, the chemical crosslinking reaction is promoted, and the thermal curing rate and bonding strength are improved.

Benefits of technology

It significantly improves the pH value of the adhesive, avoids corrosion of the board, reduces viscosity, improves coating uniformity and thermal curing efficiency, and improves the adhesive strength and board performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639421A_ABST
    Figure CN119639421A_ABST
Patent Text Reader

Abstract

The invention provides a fructose-ammonium dihydrogen phosphate environment-friendly adhesive. The fructose-ammonium dihydrogen phosphate environment-friendly adhesive is prepared from the following components in parts by weight: 60 to 80 parts of fructose, 15 to 20 parts of ammonium dihydrogen phosphate, 20.6 to 27.5 parts of water, 25.7 to 34.4 parts of a ternary composite cross-linking agent, 7.5 to 10 parts of a catalyst, 19.3 to 25.8 parts of diphenylmethane diisocyanate and 6.4 to 8.6 parts of epoxy resin, the ternary composite cross-linking agent is a mixture of silica powder, wollastonite powder and peanut protein. The pH value of the adhesive ranges from 4.0 to 4.2, and the viscosity range of the adhesive ranges from 10500 mPa.s to 1,1500 mPa.s. The pH value is relatively high, so that the embrittlement of the plate is avoided; the viscosity of the glue solution is reduced, the surface glue penetration is improved, and meanwhile, the thermocuring rate and the bonding strength are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adhesives, and specifically relates to a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive and a preparation method and application thereof. Background Art

[0002] At present, sugar-based adhesives have not yet been industrialized. Existing studies have shown that the application of sugar-based adhesives in plywood generally faces problems such as low pH value, high viscosity, easy glue penetration, and low curing efficiency. The negative impacts of specific problems include: sugar-based adhesives are usually acidic, and when the acidity is high, the bonding performance of the adhesive is better, but too strong acidity may damage the board, causing the veneer wood elements to deteriorate, thereby affecting the brittleness of the plywood and reducing its performance; in existing fructose adhesive research, the adhesive has the problem of excessive viscosity, which makes it difficult to apply the glue evenly when applying the board, affecting the bonding strength; sugar-based adhesives are prone to glue seepage during the hot pressing process due to their own weak intermolecular forces, which not only reduces the bonding strength but also affects the appearance quality of the board; the hot pressing temperature of adhesives used in traditional plywood production (such as trialdehyde-phenolic resin adhesives, urea-formaldehyde resin adhesives, and melamine formaldehyde adhesives) is usually 130°C, while the hot pressing temperature of sugar-based adhesives is generally above 150°C, which makes it difficult for sugar-based adhesives to directly replace existing adhesives. Therefore, future research on sugar-based adhesives should focus on optimizing the performance of the adhesive itself and improving the curing efficiency, so as to develop sugar-based adhesives with better performance and potential for industrial application. Summary of the invention

[0003] The purpose of the present invention is to provide a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive and a preparation method thereof. By introducing ammonium dihydrogen phosphate, a ternary composite cross-linking agent, diphenylmethane diisocyanate and an epoxy resin, the pH value is significantly increased to avoid corrosion of a plate due to excessive acidity of the adhesive, thereby causing embrittlement of the plate; the viscosity of the adhesive is reduced, the problem of surface adhesive penetration is improved, and the thermal curing rate and bonding strength are increased.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] A fructose-ammonium dihydrogen phosphate environmentally friendly adhesive comprises the following components in parts by weight: 60-80 parts of fructose, 15-20 parts of ammonium dihydrogen phosphate, 20.6-27.5 parts of water, 25.7-34.4 parts of a ternary composite cross-linking agent, and 7.5-10 parts of a catalyst. The ternary composite cross-linking agent is a mixture of silica powder, wollastonite powder and peanut protein.

[0006] Furthermore, the weight ratio of silica powder, wollastonite powder and peanut protein in the ternary composite cross-linking agent is 1:1:1.

[0007] Furthermore, the catalyst is one of p-toluenesulfonic acid, ferric chloride hexahydrate, copper sulfate, oxalic acid and citric acid.

[0008] Furthermore, it also includes 19.3-25.8 parts of diphenylmethane diisocyanate and 6.4-8.6 parts of epoxy resin.

[0009] Furthermore, the pH value of the adhesive is 4.0 to 4.2, and the viscosity ranges from 10500 to 11500 mPa·s.

[0010] A method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive comprises the following steps:

[0011] S1: fructose, diammonium phosphate and water are mixed, heated and stirred for reaction for 1 to 1.5 hours; diammonium phosphate is used to catalyze the hydrolysis and caramelization of fructose to form a low molecular weight prepolymer;

[0012] S2: adding a catalyst to step S1, heating and stirring the reaction for 1 to 2 hours to obtain a fructose diammonium phosphate solution GADP, and standing at room temperature for 24 hours; promoting the reaction of fructose diammonium phosphate by using a catalyst such as p-toluenesulfonic acid, and catalyzing fructose into 5-hydroxymethylfurfural and its derivatives under high temperature and acidic conditions;

[0013] S3: mixing silica powder, wollastonite powder and peanut protein in a weight ratio of 1:1:1 to obtain a ternary composite cross-linking agent;

[0014] S4: adding the ternary composite crosslinking agent to the fructose diammonium phosphate solution GADP in step S2 according to a solid-liquid ratio of 2.1-5.1 g:10 ml, stirring the reaction for 0.1-0.2 h, and then standing at room temperature for 10-15 min; during the curing process, the reducing sugar product after thermal degradation of fructose and the amino compound of peanut protein undergo Maillard reaction to produce a chemical crosslinking reaction, and the pH value of the prepared adhesive is significantly improved, and the viscosity of the adhesive is moderate and easy to be evenly coated on the board, thereby improving the glue seepage problem of plywood prepared by traditional fructose-based adhesives;

[0015] S5: mixing diphenylmethane diisocyanate and epoxy resin in a weight ratio of 3:1 to obtain a mixture;

[0016] S6: adding the mixture of step S5 to step S4 at a weight ratio of 0.24 to 1:4, stirring the mixture for 0.1 to 0.2 hours, stirring evenly and standing at room temperature for 10 to 15 minutes to obtain the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive.

[0017] Furthermore, in step S1, the heating temperature is 85-105° C., and the stirring rate is 100-150 r / min.

[0018] Furthermore, in step S2, the heating temperature is 85-105° C., and the stirring rate is 100-150 r / min.

[0019] Furthermore, in step S3, the stirring rate is 100-150 r / min.

[0020] The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive prepared above is applied to prepare plywood. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive is brushed on the veneer, and three layers of plywood are assembled based on the vertical texture, and hot-pressed; the double-sided glue application amount is controlled to be 140-220g / m 2 The hot pressing temperature is 130-150°C, the pressure is 1-1.5MPa, and the hot pressing time is 4-8min.

[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0022] 1. The present invention makes the whole solution acidic by adding diammonium phosphate, which promotes the generation of 5-HMF (5-hydroxymethylfurfural) and its derivatives in the system, and 5-HMF and its derivatives are considered to be an important reason for improving the water resistance of plywood; the addition of diammonium phosphate also reduces the viscosity of the glue, making it easier to apply the glue evenly. At the same time, the addition of p-toluenesulfonic acid can accelerate the thermal degradation of fructose and the formation of 5-hydroxymethylfurfural, thereby further promoting the reduction of the temperature of the pressing plate.

[0023] 2. The present invention adds a ternary composite cross-linking agent, and during the curing process, the reducing sugar product after the thermal degradation of fructose and the amino compounds of peanut protein undergo a Maillard reaction to produce a chemical cross-linking reaction to form a network structure; in order to avoid the problem of high viscosity after mixing, silica powder and wollastonite powder are added as cross-linking agents to reduce the proportion of peanut protein. At the same time, silica powder and wollastonite powder themselves have surface activity, and can undergo physical adsorption and other effects with hydroxyl groups, aldehyde groups, etc. in the sugar-based adhesive, further promoting the cross-linking reaction; ultimately, the addition of the ternary composite cross-linking agent is achieved to improve the problem of adhesive penetration on the surface of the board.

[0024] 3. To further enhance the bonding strength, the present invention introduces diphenylmethane diisocyanate and epoxy resin, which can greatly enhance the pH value of the adhesive solution when mixed with GADP. Diphenylmethane diisocyanate contains symmetrical carbon-oxygen double bonds. During the curing process, one carbon-oxygen double bond is disconnected and connected to the carbonyl group in GADP, and the other carbon-oxygen double bond is disconnected and connected to the free amino side chain in peanut protein, forming a dense structure between the three. At the same time, the Si-OH groups in silica powder and wollastonite powder and some epoxy groups in epoxy resin produce chemical bonding reactions, so that the two-phase interface has good adhesion and enhances the bonding strength.

[0025] 4. The pH value of the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive prepared by the present invention is increased from 1.5 to above 4.0, and the viscosity range is 10500-11500 mPa·s. It is easy to apply evenly on the board and can be hot-pressed at 130-150°C. It not only improves the glue seepage problem of plywood prepared by traditional fructose-based adhesives, but also avoids the problem of corrosion of the board due to excessive acidity of the glue, causing embrittlement of the board. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 -Use unmodified sugar-based adhesive to coat the board;

[0027] Figure 2 -Use the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive described in Example 3 to coat the board. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive, comprising the following steps:

[0031] S1: Mix 60g fructose, 15g diammonium phosphate and 20.6g water, and heat and stir at 85°C at a rate of 100r / min for 1 to 1.5h;

[0032] S2: Add 7.5 g of p-toluenesulfonic acid to step S1, heat and stir at 85°C at a rate of 100 r / min for 1 h to obtain a fructose diammonium phosphate solution GADP, and let stand at room temperature for 24 h;

[0033] S3: Silica powder, wollastonite powder and peanut protein are mixed uniformly in a weight ratio of 1:1:1 to obtain a ternary composite crosslinking agent; the ternary composite crosslinking agent is added to the fructose ammonium dihydrogen phosphate solution GADP in step S2 in a solid-liquid ratio of 2.1 g:10 ml, and the reaction is stirred at a rate of 100 r / min for 0.1 h, and then allowed to stand at room temperature for 10 min;

[0034] S4: mixing diphenylmethane diisocyanate and epoxy resin in a weight ratio of 3:1 to obtain a mixture;

[0035] S5: adding the mixture of step S4 to step S3 at a weight ratio of 0.24:4, stirring at a rate of 100 r / min for 0.1 h, stirring evenly and standing at room temperature for 10 min to obtain the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive.

[0036] Example 2

[0037] This embodiment provides a method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive, comprising the following steps:

[0038] S1: Mix 80g fructose, 20g diammonium phosphate and 27.5g water, and heat and stir at 105°C and 150r / min for 1.5h;

[0039] S2: Add 10 g of p-toluenesulfonic acid to step S1, heat and stir at 105°C at a rate of 150 r / min for 2 h to obtain a fructose diammonium phosphate solution GADP, and let stand at room temperature for 24 h;

[0040] S3: Silica powder, wollastonite powder and peanut protein are mixed uniformly in a weight ratio of 1:1:1 to obtain a ternary composite crosslinking agent; the ternary composite crosslinking agent is added to the fructose ammonium dihydrogen phosphate solution GADP in step S2 in a solid-liquid ratio of 5.1 g:10 ml, and the reaction is stirred at a rate of 150 r / min for 0.2 h, and then allowed to stand at room temperature for 15 min;

[0041] S4: mixing diphenylmethane diisocyanate and epoxy resin in a weight ratio of 3:1 to obtain a mixture;

[0042] S5: Add the mixture in step S4 to step S3 at a weight ratio of 1:4, stir at a rate of 150 r / min for 0.2 h, and let stand at room temperature for 15 min after stirring evenly to obtain the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive.

[0043] Example 3

[0044] This embodiment provides a method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive, comprising the following steps:

[0045] S1: Mix 70g fructose, 18g diammonium phosphate and 25g water, and heat and stir at 95°C at a rate of 120r / min for 1.2h;

[0046] S2: Add 8.5 g of p-toluenesulfonic acid to step S1, heat and stir at 95°C at a rate of 130 r / min for 1.5 h to obtain a fructose ammonium dihydrogen phosphate solution GADP, and let stand at room temperature for 24 h;

[0047] S3: Silica powder, wollastonite powder and peanut protein are mixed uniformly in a weight ratio of 1:1:1 to obtain a ternary composite crosslinking agent; the ternary composite crosslinking agent is added to the fructose ammonium dihydrogen phosphate solution GADP in step S2 in a solid-liquid ratio of 3g:10ml, and the reaction is stirred at a rate of 150r / min for 0.15h, and then allowed to stand at room temperature for 12min;

[0048] S4: mixing diphenylmethane diisocyanate and epoxy resin in a weight ratio of 3:1 to obtain a mixture;

[0049] S5: Add the mixture of step S4 to step S3 at a weight ratio of 1:4, stir at a rate of 150 r / min for 0.15 h, stir evenly and let stand at room temperature for 12 min to obtain the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive.

[0050] Comparative Example 1

[0051] The difference from Example 1 is that steps S3, S4 and S5 are missing, that is, specifically: S1: 60 g fructose, 15 g diammonium phosphate and 20.6 g water are mixed, and heated and stirred at a temperature of 85° C. at a rate of 100 r / min for 1 to 1.5 h;

[0052] S2: Add 7.5 g of p-toluenesulfonic acid to step S1, heat and stir at 85° C. and a rate of 100 r / min for 1 h to obtain a fructose diammonium phosphate solution GADP, and let stand at room temperature for 24 h; obtain an unmodified sugar-based adhesive.

[0053] Comparative Examples 2-5

[0054] The difference from Example 1 is that in step S2, p-toluenesulfonic acid is replaced by ferric chloride hexahydrate, copper sulfate, oxalic acid, and citric acid, respectively, and the rest is the same as Example 1.

[0055] Comparative Examples 6-7

[0056] The difference from Example 1 is that the addition amount of p-toluenesulfonic acid in step S2 is 5% and 15% respectively, and the others are the same as Example 1.

[0057] Comparative Examples 8-10

[0058] The difference from Example 1 is that in step S3, the solid-to-liquid ratios of the ternary composite cross-linking agent and the fructose diammonium phosphate solution GADP are 2.1 g:10 ml, 3.3 g:10 ml, and 5.1 g:10 ml, respectively, that is, GADP:PPI:silica powder:wollastonite powder are 10:0.7:0.7:0.7, 10:1.1:1.1:1.1, and 10:1.7:1.7:1.7, respectively, and the rest are the same as Example 1.

[0059] Comparative Examples 11-13

[0060] The difference from Example 1 is that in step S5, the weight ratios of the mixture in step S4 and GADP are 0.24:4, 0.51:4, and 0.76:4, respectively, that is, GADP:complex crosslinking agent:MDI:EP are 4:1:0.18:0.06, 4:1:0.38:0.13, and 4:1:0.57:0.19, respectively, and the rest are the same as Example 1.

[0061] The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive prepared in Examples 1-3 and Comparative Examples 1-12 was applied to the veneer, and three layers of plywood were assembled in a vertical grain manner and hot-pressed; the double-sided glue application amount was controlled to be 140 g / m 2 The hot pressing temperature is 150℃, the pressure is 1MPa, and the hot pressing time is 8min.

[0062] Comparative Examples 14-16

[0063] The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive prepared in Example 1 was applied on the veneer, and three layers of plywood were assembled in a vertical grain manner and hot-pressed; the double-sided glue application amount was controlled to be 140 g / m 2 The hot pressing temperatures were 110°C, 130°C, and 170°C, the pressure was 1MPa, and the hot pressing time was 8min.

[0064] The dry shear strength, dry wood breakage rate, wet shear strength and wet wood breakage rate of each embodiment and comparative example were tested. The results are shown in Table 1.

[0065] Table 1

[0066]

[0067]

[0068] Comparison of Example 1 and Comparative Example 1 shows that the unmodified sugar-based adhesive has a poor effect.

[0069] By comparing Example 1 with Comparative Examples 2-5, it can be seen that taking p-toluenesulfonic acid as the catalyst has the best effect.

[0070] By comparing Example 1 and Comparative Examples 6-7, it can be seen that the best effect is achieved when the toluenesulfonic acid is used as a catalyst at a dosage of 10%.

[0071] By comparing Example 2 and Comparative Examples 8-10, it can be seen that the more the amount of composite crosslinking agent added, the better the bonding performance. When GADP:PPI:silica powder:wollastonite powder is 10:1.7:1.7:1.7, the viscosity of the adhesive is too high to be evenly coated on the board, resulting in a decrease in the shear resistance of the board. Among these four groups, only when GADP:PPI:silica powder:wollastonite powder=10:0.8:0.8:0.8 has a moderate viscosity of 7600-8000mPa·s, so the ratio of 10:0.8:0.8:0.8 is selected, and the best ratio is 10:0.8:0.8:0.8.

[0072] By comparing Example 3 and Comparative Examples 11-13, it can be seen that the more the amount of MDI-EP composite compound added, the higher the bonding strength, so the ratio of 4:1:0.75:0.25 is selected, and the best ratio is obtained as 4:1:0.75:0.25.

[0073] By comparing Example 3 and Comparative Examples 14-16, it can be seen that when the temperature increases from 150°C to 170°C, the bonding strength decreases significantly. It can be seen that a hot pressing temperature that is too high (170°C) causes the wood unit of the board to be destroyed, thereby causing a decrease in bonding strength. A hot pressing temperature that is too high may also cause the wood to be brittle and easy to break.

[0074] Based on the above performance test results, it can be seen that the fructose-ammonium dihydrogen phosphate environmentally friendly adhesives prepared in Examples 1-3 have good viscosity, pH value, bonding strength and other properties. However, since the necessary technical solutions were not adopted in the comparative examples, the corresponding performance tests were significantly worse than those of the examples. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.

[0075] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A fructose-ammonium dihydrogen phosphate environmentally friendly adhesive, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of fructose, 15-20 parts of ammonium dihydrogen phosphate, 20.6-27.5 parts of water, 25.7-34.4 parts of a ternary composite cross-linking agent, and 7.5-10 parts of a catalyst. The ternary composite cross-linking agent is a mixture of silica powder, wollastonite powder and peanut protein.

2. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 1, characterized in that: The weight ratio of silica powder, wollastonite powder and peanut protein in the ternary composite cross-linking agent is 1:1:

1.

3. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 1, characterized in that: The catalyst is one of p-toluenesulfonic acid, ferric chloride hexahydrate, copper sulfate, oxalic acid and citric acid.

4. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 1, characterized in that: It also includes 19.3-25.8 parts of diphenylmethane diisocyanate and 6.4-8.6 parts of epoxy resin.

5. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 1, characterized in that: The pH value of the adhesive is 4.0~4.2, and the viscosity range is 10500~11500mPa·s.

6. A method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive, characterized in that: The steps include: S1: Mix fructose, diammonium phosphate and water, and heat and stir to react for 1-1.5h; S2: adding a catalyst to step S1, heating and stirring the reaction for 1-2 hours to obtain a fructose ammonium dihydrogen phosphate solution GADP, and standing at room temperature for 24 hours; S3: mixing silica powder, wollastonite powder and peanut protein in a weight ratio of 1:1:1 to obtain a ternary composite cross-linking agent; S4: adding the ternary composite crosslinking agent to the fructose diammonium phosphate solution GADP in step S2 according to a solid-liquid ratio of 2.1-5.1 g:10 ml, stirring the reaction for 0.1-0.2 h, and then standing at room temperature for 10-15 min; S5: mixing diphenylmethane diisocyanate and epoxy resin in a weight ratio of 3:1 to obtain a mixture; S6: adding the mixture of step S5 to step S4 at a weight ratio of 0.24 to 1:4, stirring the mixture for 0.1 to 0.2 h, stirring evenly and standing the mixture at room temperature for 10 to 15 min to obtain the fructose-ammonium dihydrogen phosphate environmentally friendly adhesive.

7. The method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 4, characterized in that: In step S1, the heating temperature is 85-105° C., and the stirring rate is 100-150 r / min.

8. The method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 4, characterized in that: In step S2, the heating temperature is 85-105° C., and the stirring rate is 100-150 r / min.

9. The method for preparing a fructose-ammonium dihydrogen phosphate environmentally friendly adhesive according to claim 4, characterized in that: The stirring rate in step S3 is 100-150 r / min.

10. The fructose-ammonium dihydrogen phosphate environmentally friendly adhesive prepared according to any one of claims 1 to 9 is used in the preparation of plywood, characterized in that: Apply fructose-ammonium dihydrogen phosphate environmentally friendly adhesive on the veneer, assemble 3 layers of plywood based on vertical texture, and hot press to form; control the double-sided glue application amount to 140~220g / m 2 The hot pressing temperature is 130~150℃, the pressure is 1~1.5MPa, and the hot pressing time is 4~8min.

Citation Information

Patent Citations

  • Ultrahigh solid content environmentally-friendly adhesive for plywood, preparation method and applications thereof

    CN110684485A

  • Glue-permeation-free plant protein sucrose-based environment-friendly adhesive for plywood as well as preparation method and application of glue-permeation-free plant protein sucrose-based environment-friendly adhesive

    CN113861936A

  • Cottonseed protein-glycosyl environment-friendly adhesive as well as preparation method and application thereof

    CN114350313A